Структура системы управления, обработки и формирования сигналов при акустическом зондировании атмосферы - Ибраимов, И. К. (ХНУРЕ, 2019)
Modern information measuring systems are based on microprocessors or personal computers. The main process of information processing is performed using special or standard software. The task of the developer of electronic equipment is to create electronic units for processing analog signals from prima-ry measuring transducers, and reducing their parameters to optimal ones, at which information is converted into digital form with minimal losses using ana-log digital converters. The paper presents the scheme of the control unit piezoe-lectric irradiators.